2008
DOI: 10.1097/hjh.0b013e3282fe6eaa
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of angiotensin II receptor subtype 1A in the development of two-kidney, one-clip hypertension: study in angiotensin II receptor subtype 1A knockout mice

Abstract: Objective The present study was performed to examine in two-kidney, one clip (2K1C) Goldblatt hypertensive mice, first, the relative contribution of angiotensin II (ANG II) receptor subtypes 1A (AT1A) and 1B (AT1B); second, the role of ANG II type 2 (AT2) receptors in the development of hypertension in wild-type (AT1A+/+) and AT1A receptor knockout (AT1A−/−) mice and third, the role of increased nitric oxide synthase (NOS) activity in counteracting the hypertensinogenic action of ANG II in this model. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 45 publications
9
56
0
Order By: Relevance
“…Cervenka et al (3) recently inhibited NOS in 2K1C mice, which resulted in a BP increase, indicating an increased dependency of NO release during renovascular hypertension. In AT 1a -deficient mice, however, the BP increase induced by NOS inhibition was similar in 2K1C and sham, demonstrating that the increased NO release in wild-type 2K1Cs was dependent on a functional AT 1a receptor (3). Taken together, these reports indicate that NO release is directly linked to AT 1a receptor stimulation.…”
Section: Discussionsupporting
confidence: 54%
“…Cervenka et al (3) recently inhibited NOS in 2K1C mice, which resulted in a BP increase, indicating an increased dependency of NO release during renovascular hypertension. In AT 1a -deficient mice, however, the BP increase induced by NOS inhibition was similar in 2K1C and sham, demonstrating that the increased NO release in wild-type 2K1Cs was dependent on a functional AT 1a receptor (3). Taken together, these reports indicate that NO release is directly linked to AT 1a receptor stimulation.…”
Section: Discussionsupporting
confidence: 54%
“…With regard to cardiac hypertrophy, recent studies have demonstrated that the severity of cardiac hypertrophy in ANG II-dependent models of hypertension is exclusively dependent on BP level [20,28,29]. Because the RAS-dependent antihypertensive therapy in our present study decreased SBP even below levels observed in sham-operated normotensive HanSD rats, the addition of the ET A receptor antagonist could not exhibit further BP reduction and, therefore, additional cardioprotective effects cannot be expected.…”
Section: Discussionmentioning
confidence: 42%
“…Binding of ANG II to the AT 1 receptor on the cell surface induces rapid internalization of the ligand-receptor complex (46,59,99). Chronic AT 1 receptor blockade or AT 1 receptor deletion significantly reduces renal content of ANG II, suggesting that receptor-mediated uptake of ANG II contributes directly to intracellular peptide levels and/or stimulates intracellular synthesis (10,13,57,58,63,78). Our preliminary studies find that ANG II administration restores the depleted levels of ANG II in the kidney of tissue ACE knockout mice to that of the wild-type mice (64).…”
Section: Intracellular Formationmentioning
confidence: 99%